An efficient closed-form design method for nearly perfect reconstruction of non-uniform filter bank. (March 2016) - Kumar, A.; Pooja, R.; Singh, G.K.
Abstract: In this paper, an efficient closed form method for the design of multi-channel nearly perfect reconstruction of non-uniform filter bank with the prescribed stopband attenuation and channel overlapping is presented. In this method, the design problem of multi-channel non-uniform filter bank (NUFB) is considered as the design of a prototype filter whose magnitude response at quadrature frequency is 0.707, which is exploited for finding the optimum passband edge frequency through empirical formula instead of using single or multivariable optimization technique. Two main attributes used in assessing the performance of filter bank are peak reconstruction error ( PRE ) and computational time ( CPU time ). As compared to existing methods, this method is very simple and easy to implement for NUFBs. To implement this algorithm, a Matlab program has been developed, and several examples are presented to illustrate the performance of proposed method. Highlights: A closed form design method for designing of non-uniform filter bank. An empirical relation is developed for optimum passband edge frequency. A comparative study of different window functions.